Assess the Complaint Handling and Service Recovery Practices in Hotels: The Case of Debark Town, Ethiopia - Adino Mandie Fisha (International Journal of Sustainability, 2025)
This study aims to assess the complaint-handling and service recovery practices of hotels in Debark town. The service sector is an important component worldwide, encompassing transportation, communication, the hotel industry, tourism, etc. The target group for this study consisted of patrons, staff, and managers of the Simien National Park Hotel. Data were collected using a non-probability sampling technique, specifically convenience sampling for customers. The researcher selected a sample of 81 representatives, including one manager, to determine the sample size of the study. Of these, 68 were customers of the Simien National Park Hotel, and the remaining 12 were employees. For this study, the researcher used both primary and secondary sources of data, in addition to qualitative and quantitative data types. The research adopted a descriptive research design, as it is appropriate for presenting phenomena as they exist in the present time. Furthermore, the study emphasized the importance of effective service recovery practices, as handling customer complaints is crucial for maintaining loyalty and satisfaction. Hotels that fail to respond promptly to guest concerns often risk negative word-of-mouth publicity, which can severely affect their reputation and profitability. In contrast, hotels that actively implement structured complaint-handling mechanisms are more likely to turn dissatisfied customers into loyal patrons. The research also highlighted the role of hotel employees, who serve as the first point of contact in resolving customer grievances. Their responsiveness, empathy, and problem-solving abilities were found to significantly influence overall guest perceptions. Additionally, the study acknowledged that managers play a vital role in setting service standards and ensuring consistent implementation of recovery strategies. Hence, the findings are expected to provide valuable insights for hotel management in Debark town, guiding them toward improving service quality and competitiveness in the hospitality industry.
Keywords: Debark; Semien park; service; service recovery and compliant handling